Gereja Mula-Mula Menyikapi Perbedaan dan Konflik Berdasarkan Kisah Para Rasul 15:1-34: Sebuah Refleksi bagi Gereja Toraja Mamasa - Yulianus Toding (CHARISTHEO: Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
The background of this article is the conflict and differences in the Toraja Mamasa Church after the Bikker-Geleijnse. Acts 15:1-34 tells about how the early church resolved conflicts due to differences. This similarity of experience prompted the authors to examine the text of Acts 15:1-34 as reflective material in dealing with differences in the Toraja Mamasa Church after Bikker-Geleijnse. The research method used is narrative criticism. The research question that the author poses is how did the early church respond to conflict and differences as a reflective material for the Toraja Mamasa Church? The author carries out this research by describing the traces of Bikker and Geleijnse's mission in Mamasa, the background of the conflict in the early church, interpreting the text of Acts 15:1-34, and constructing a reflection to resolve conflicts and differences in the Toraja Mamasa Church.The research method used is narrative criticism.  The author finds that the early church faced conflicts and differences with a middle-ground perspective. The church gives freedom to the context of carrying out its own ethnic laws and rules while at the same time emphasizing Christian ethics as a standard of God's holiness. This action then spurred the Toraja Mamasa Church to have a contextual perspective while at the same time respecting the holiness of God. AbstrakLatar belakang artikel ini adalah konflik dan perbedaan di Gereja Toraja Mamasa pasca Bikker-Geleijnse. Kisah Para Rasul 15:1-34 menceritakan tentang bagaimana gereja mula-mula menyelesaikan konflik akibat perbedaan. Kesamaan pengalaman ini mendorong penulis untuk mengkaji teks Kisah Para Rasul 15:1-34 sebagai bahan reflektif menghadapi perbedaan di Gereja Toraja Mamasa pasca Bikker-Geleijnse. Metode penelitian yang digunakan adalah kritik naratif. Pertanyaan penelitian yang penulis ajukan adalah bagaimana gereja mula-mula menyikapi konflik dan perbedaan, sebagai bahan reflektif bagi Gereja Toraja Mamasa? Penulis melaksanakan penelitian ini dengan mendeskripsikan jejak misi Bikker dan Geleijnse di Mamasa, latar belakang konflik dalam gereja mula-mula, menginterpretasi teks Kisah Para Rasul 15:1-34, dan mengonstruksikan sebuah refleksi untuk menyelesaikan konflik dan perbedaan di Gereja Toraja Mamasa. Penulis menemukan bahwa gereja mula-mula menghadapi konflik dan perbedaan dengan perspektif jalan tengah. Gereja memberi kebebasan kepada konteks menyelenggarakan hukum dan aturan etnisnya masing-masing, sekaligus menekankan etika Kristen sebagai standar kekudusan Allah. Tindakan ini kemudian memacu Gereja Toraja Mamasa untuk berwawasan kontekstual, sekaligus menghormati kekudusan Allah. Kata Kunci: konflik gereja, gereja mula-mula, Gereja Toraja Mamasa, sidang di Yerusalem